EFEKTIVITAS PEMBELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN KEMAMPUAN MENULIS ILMIAH PADA SISWA SMK XI - Nurul Aini; Wildatus Saputeri; Yanti Linarsih; Laili Amalia (STKIP Subang, 2026)
This study aims to analyze the effectiveness of Indonesian language learning in improving scientific writing skills among eleventh-grade vocational high school students. The research employed a literature review method by examining relevant journals and scientific sources. The findings show that Indonesian language learning plays an important role in developing students' critical thinking, written communication, and scientific writing skills. Learning strategies such as Project-Based Learning (PjBL) are effective in helping students produce scientific papers systematically. Learning success is influenced by students' motivation, literacy skills, teachers' roles, and the availability of learning resources. However, students still face challenges in developing ideas, low reading interest, and limited understanding of scientific writing structures.